Perceived parenting and identification with all humanity: Insights from England and Germany - Hagel, Minne Luise; Trutzenberg, Friedemann; Eid, Michael (Frontiers in Psychology, 2022)
In the past decade, Identification With All Humanity (IWAH) has been found to predict several positive behavioral outcomes like volunteering, a willingness to contribute to humanitarian relief, and cooperative health behavior during the COVID-19 pandemic. However, to this day, little is known about how individual differences in IWAH emerge. Therefore, the present study aimed to explore whether there is a relationship between individuals’ upbringing and their IWAH. For this purpose, data on IWAH, remembered parenting behavior (RPB), and remembered parental attachment assessed by 3056 individuals (1517 from Germany and 1539 from England) were analyzed. Structural equation models were used to A) analyze the correlations between RPB, attachment, and IWAH and to B) test whether single facets of RPB and attachment could significantly predict IWAH when controlling for the other facets in a latent regression analysis. The facets of positive RPB correlated significantly positively with the two facets of IWAH (global self-definition and global self-investment) and explained between 4.1 and 7% of their variance. Surprisingly, in the English sample, two facets of negative RPB also correlated significantly positively with IWAH. The explained variance in IWAH being significant but small, it is argued that parents’ attitudes or behavior specifically related to IWAH could have a greater impact on IWAH than more unspecific parenting behavior. For instance, we discovered that the extent to which participants perceived their parents as global citizens explained about one third of the variance in their own identification as global citizens. Fostering IWAH could constitute an effective approach to tackle important global challenges. Therefore, more research is needed to test the generalizability of the results and to further analyze the roots of people’s IWAH.